Physical and chemical water parameters and Streptococcus spp. occurrence in intensive tilapia farming in the State of Espírito Santo, Brazil - doi: 10.4025/actascibiolsci.v35i1.11797 - Maria Isabel Suhet; Ruben Pablo Schocken-Iturrino (Acta Scientiarum: Biological Sciences, 2012)
This study evaluated the influence of intensive farming of tilapia on physical and chemical parameters and on the occurrence of Streptococcus spp. in the water of the lake and of cages. Throughout a year, monthly samplings were taken in the rainy and dry seasons for a year, at two sampling sites, lake and net cages. For the determination of water quality, physical and chemical water parameters were evaluated and compared to the standards established by Conama Resolution no. 357/2005. The presence of Streptococcus spp. in the water was determined by plating on blood Agar and biochemical screening. Mean values of water parameters were tested using the Kruskal-Wallis test comparing sampling sites and seasons. Ammoniacal nitrogen (ammoniacal-N), total phosphorus (total-P) levels and occurrence of Streptococcus spp. have increased in the water of the net cages. The mean values of several parameters have decreased during the rainy period, except for pH, temperature and ammoniacal-N. Total-P and dissolved oxygen levels, during dry and rainy periods, respectively, exceeded the standard established for freshwater class 2, recommended for aquaculture, which can be harmful to the fish. Therefore, constant monitoring of the physical,chemical and microbiological water parameters is recommended since the Juara lake is also used for recreational purposes.